Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140066
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Control and Metabolism in Heat Stress

Abstract: This review provides an in-depth update on the impact of heat stress on cerebrovascular functioning. The regulation of cerebral temperature, blood flow, and metabolism are discussed. We further provide an overview of vascular permeability, the neurocognitive changes, and the key clinical implications and pathologies known to confound cerebral functioning during hyperthermia. A reduction in cerebral blood flow (CBF), derived primarily from a respiratory-induced alkalosis, underscores the cerebrovascular changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 474 publications
(600 reference statements)
1
76
1
1
Order By: Relevance
“…Impairments induced in cognitive performance during heat stress have been suggested to depend on the complexity and/or duration of cognitive tasks17181920 as well as the severity and duration of heat stress21. We previously demonstrated, even in ‘simple’ auditory oddball tasks, that hyperthermia reduced the cognitive processing index (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairments induced in cognitive performance during heat stress have been suggested to depend on the complexity and/or duration of cognitive tasks17181920 as well as the severity and duration of heat stress21. We previously demonstrated, even in ‘simple’ auditory oddball tasks, that hyperthermia reduced the cognitive processing index (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Mild hyperthermia reduces cerebral perfusion521, indicating that restricted cerebral perfusion contributes to an impaired brain neural network and reduced cognitive processing. We previously demonstrated that passive heat stress decreased ICA blood flow, but increased ECA for heat dissipation15.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis presented by D'haeseleer et al [31] states that there is widespread cerebral hypoperfusion in PwMS, which is associated with cognitive dysfunction and fatigue. These symptoms could intensify with hyperthermia [32]. Additionally, there is evidence that acute and chronic exercises increase brain perfusion [33].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient cerebral perfusion, and thus oxygen delivery, is the primary mechanism for loss of consciousness during central hypovolemia (Meendering et al, 2005; Van Lieshout et al, 2003). It is noteworthy that passive heat stress itself reduces cerebral perfusion (Bain et al, 2013; Brothers et al, 2009b; Fan et al, 2008; Fujii et al, 2008; Lucas et al, 2008, 2010; Nelson et al, 2011b; Ogoh et al, 2013, 2014; Ross et al, 2012; Schlader et al, 2013a; Wilson et al, 2002b, 2006); see the following citations for comprehensive reviews on this topic (Bain et al, 2015; Crandall and Wilson, 2014). After a threshold is achieved, the magnitude of the reduction in cerebral perfusion is related to the severity of the heat stress (Bain et al, 2015).…”
Section: Mechanisms Of Orthostatic Intolerance During Heat Stressmentioning
confidence: 99%
“…It is noteworthy that passive heat stress itself reduces cerebral perfusion (Bain et al, 2013; Brothers et al, 2009b; Fan et al, 2008; Fujii et al, 2008; Lucas et al, 2008, 2010; Nelson et al, 2011b; Ogoh et al, 2013, 2014; Ross et al, 2012; Schlader et al, 2013a; Wilson et al, 2002b, 2006); see the following citations for comprehensive reviews on this topic (Bain et al, 2015; Crandall and Wilson, 2014). After a threshold is achieved, the magnitude of the reduction in cerebral perfusion is related to the severity of the heat stress (Bain et al, 2015). For example, during mild to moderate heating, when internal temperature increases between ~0.5 and 1.2 °C, cerebral perfusion either does not change or only modestly decreases (Low et al, 2009; Lucas et al, 2008; Schlader et al, 2013a; Wilson et al, 2002b, 2006).…”
Section: Mechanisms Of Orthostatic Intolerance During Heat Stressmentioning
confidence: 99%